SARS‐CoV‐2 induced HDL dysfunction may affect the host's response to and recovery from COVID‐19 - Hayder M. Al‐kuraishy; Nawar R. Hussien; Marwa S. Al‐Niemi; Esraa H. Fahad; Ali K. Al‐Buhadily; Ali I. Al‐Gareeb; Sadiq M. Al‐Hamash; Christos Tsagkaris; Marios Papadakis; Athanasios Alexiou; Gaber El‐Saber Batiha (Immunity, Inflammation and Disease)
Abstract Introduction Covid‐19 is linked with the development of cardio‐metabolic disorders, including dyslipidemia, dysregulation of high‐density lipoprotein (HDL), and low‐density lipoprotein (LDL). Furthermore, SARS‐Co‐2 infection is associated with noteworthy changes in lipid profile, which is suggested as a possible biomarker to support the diagnosis and management of Covid‐19. Methods This paper adopts the literature review method to obtain information about how Covid‐19 affects high‐risk group patients and may cause severe and critical effects due to the development of acute lung injury and acute respiratory distress syndrome. A narrative and comprehensive review is presented. Results Reducing HDL in Covid‐19 is connected to the disease severity and poor clinical outcomes, suggesting that high HDL serum levels could benefit Covid‐19. SARS‐CoV‐2 binds HDL, and this complex is attached to the co‐localized receptors, facilitating viral entry. Therefore, SARS‐CoV‐2 infection may induce the development of dysfunctional HDL through different mechanisms, including induction of inflammatory and oxidative stress with activation of inflammatory signaling pathways. In turn, the induction of dysfunctional HDL induces the activation of inflammatory signaling pathways and oxidative stress, increasing Covid‐19 severity. Conclusions Covid‐19 is linked with the development of cardio‐metabolic disorders, including dyslipidemia in general and dysregulation of high‐density lipoprotein and low‐density lipoprotein. Therefore, the present study aimed to overview the causal relationship between dysfunctional high‐density lipoprotein and Covid‐19.